Functional movement screening tests for the prediction of injuries in volleyball: A qualitative study - Tabatabaei, S. M.; Daneshmandi, H.; Norasteh, A. A.; Sharif Nia, H. (Annals of Applied Sport Science, 2018)
Background. There is little evidence to support the comprehensiveness of FMS in sports populations to predict injuries. Ignoring rapid decelerations and high eccentric forces which may be characteristics of high risk for injury are evident in these tests. With this in mind, it seems logical to use tests to assess the performance of athletes so as to evaluate speed components as well as to identify the potential risk factors for injury. This can be a good complement to FMS. Objectives. This study aimed to identify functional movement screening tests to predict injuries in volleyball. Methods. In this descriptive study, 20 high-level experts in volleyball were selected through purposive sampling. The data were collected in 2017 through semi-structured interviews and field notes. The interview transcripts were encoded using MAXQDA10 software®. To extract the categories and subjects, the thematic analysis approach was used. Results. In the first analysis process, the initial codes were extracted and finally, 38 of the 82 existing potential tests were identified. Then, after various stages of determining the validity and reliability of 12 tests—deep squat, inline lunge, trunk stability push up, rotary stability, shoulder mobility, triple hop for distance, hexagon, lateral lunge, triple jump for distance, sidearm medicine ball throw, closed kinetic chain upper extremity and squat jump—were identified for inclusion in this tool. Conclusions. Based on the results of the interviews, it could be concluded that the interviewees` choices were based more on the tests` similarity with the type of movement patterns and performance capabilities in volleyball and considering the anatomical areas prone to injury as well.